An Ethical and Legal Approach to Student Smoking Behavior in the Context of Education and Family Responsibility - Anwar, Ahmad Faridz; Apriana, Adistia Lulu; Kholiq, Achmad; Marzuban, Robith (CV. Strata Persada Academia, 2025)
This research examines the ethical and legal framework for addressing student smoking in Indonesia, highlighting the roles of education and family. Influencing factors include internal aspects like curiosity and peer pressure, as well as external elements such as easy cigarette access and aggressive marketing. Using a qualitative descriptive approach and literature study, data were analyzed through content analysis to explore themes of smoking behavior, educational ethics, family responsibility, and tobacco regulation. The research draws on moral education theory and legal perspectives on tobacco control. Findings indicate that integrating moral education into school curricula increases student awareness of smoking risks. Likewise, positive parental role modeling and communication influence children’s attitudes toward smoking. Legally, strict enforcement of sales bans to minors and regulation of tobacco advertising are vital. The study concludes that combating student smoking requires collaboration among government, schools, and families. A holistic approach combining ethical education with legal enforcement is key to cultivating a smoke-free younger generation.